2006
DOI: 10.1111/j.1750-3841.2006.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Infrared Dehydration of Onions

Abstract: Dehydrated onions are commonly dried with convection heating, which is inefficient and costly. This study compared the drying and quality characteristics of onion dried with catalytic infrared (CIR) heating and forced air convection (FAC) heating. Sliced high‐solids onions were dehydrated under 9 conditions: CIR heating with and without air recirculation, and FAC each operated at 60, 70, and 80 °C. In general, CIR both with and without air recirculation had higher maximum drying rates, shorter drying times, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 16 publications
4
42
0
Order By: Relevance
“…The dramatic drop in drying rate after reaching the peak was mainly because following moisture removal in the surface layer, the speed of further drying is limited to the rate of moisture diffusion from the interior of the slice to the surface layer. This did not show a constant drying rate period, which agreed with many other infrared drying studies such as the infrared drying of onions and strawberries (Gabel et al, 2006;Shih et al, 2008). In general, thin slices showed higher drying rates than thick slices.…”
Section: Moisture Reduction and Drying Kineticssupporting
confidence: 89%
See 2 more Smart Citations
“…The dramatic drop in drying rate after reaching the peak was mainly because following moisture removal in the surface layer, the speed of further drying is limited to the rate of moisture diffusion from the interior of the slice to the surface layer. This did not show a constant drying rate period, which agreed with many other infrared drying studies such as the infrared drying of onions and strawberries (Gabel et al, 2006;Shih et al, 2008). In general, thin slices showed higher drying rates than thick slices.…”
Section: Moisture Reduction and Drying Kineticssupporting
confidence: 89%
“…An empirical Page model was chosen to fit the drying curves in this study due to its simplicity and good performance of describing drying thin-layer fruits and vegetables in many reported works (Togrul, 2005(Togrul, , 2006Gabel et al, 2006;Kumar et al, 2006;Sacilik and Elicin, 2006). The model was stated as:…”
Section: Modeling Of Drying Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic IR (CIR) emitter is powered by natural gas or propane to produce thermal radiant energy through a catalytic reaction with a mesh catalyst pad built into CIR emitters. The radiation energy that is generated has a peak wavelength in the range of medium-and far-IR which matches reasonably well with three of the absorption peaks of water, resulting in rapid heating and moisture removal from high-moisture foods (Pan and McHugh, 2004;Gabel et al, 2006). Continuous IR heating mode, in this study, is achieved by maintaining constant radiation intensity through continuous supply of natural gas to CIR emitters.…”
Section: Introductionmentioning
confidence: 54%
“…Simple empirical drying model, page model, was used to fit the drying curves in this study based on reported works on drying thin-layer fruits and vegetables (Togrul, 2005;Gabel et al, 2006;Kumar et al, 2006;Sacilik and Elicin, 2006;Togrul, 2006).…”
Section: Modeling Of Drying Kineticsmentioning
confidence: 99%